To simplify the expression \( r^{-4} p^{-8} \), we can rewrite it in terms of positive exponents.
Using the rule that \( x^{-n} = \frac{1}{x^n} \), we have:
\[ r^{-4} = \frac{1}{r^4} \] \[ p^{-8} = \frac{1}{p^8} \]
Therefore, the expression can be rewritten as:
\[ r^{-4} p^{-8} = \frac{1}{r^4} \cdot \frac{1}{p^8} = \frac{1}{r^4 p^8} \]
So, the simplified form of the expression \( r^{-4} p^{-8} \) is:
\[ \frac{1}{r^4 p^8} \]
The correct answer from the options given is: the fraction with numerator 1 and denominator r to the 4th power p to the 8th power.